Enfoque de cadena de valor y su impacto en la cadena productiva del Sacha Inchi en los distritos de Tarapoto y Lamas, año 2013 - Pezo Castillo, Claudia Milagros (2015)
This work exposes an investigation which intention is to determine of what way the approach of chain of value affects the productive chain of the sacha inchi Tarapoto's districts and Lamas, year 2013. The selected design is not experimental research, since the study involved the observation made in its natural condition without intervention of the researcher; It is correlational; since the relationship and impact between the two variables described in a particular context; is measured by quantitative, measurable or quantifiable since information was used, that is based on the numerical measurement and statistical analysis; its purpose is basic and temporal scope as the research was cross because it was made in a single year, 2013. The used sample was constituted by 22 persons dedicated to the production, transformation, services and commercialization; to whom the survey was applied as instrument of investigation, which was validated across experts' Judgments by specialists in the topic. The result of this investigation is favorable as for the impact that produces the approach of chain of value, since the raised hypothesis was demonstrated where the approach of chain of value affects positively the productive chain of the sacha inchi Tarapoto's districts and Lamas year 2013; being observed that to 99 and 95 % of confidence, the systemic vision and level of commitment are significant in the productive chain of the sacha inchi.